Parathyroidectomy for tertiary hyperparathyroidism after second kidney transplantation: a case report - Masaki, Chiaki (CEN Case Rep, 2020)
Successful kidney transplantation usually resolves secondary hyperparathyroidism (SHPT). However, some patients fail to normalize, and their condition is often referred to as tertiary hyperparathyroidism (THPT). Surgical consensus on the timing of post-transplant parathyroidectomy (PTX) for THPT has not been reached. Herein, we report a case of a 58-year-old post-transplant woman, considering the concrete timing of PTX for both SHPT and THPT. She initiated hemodialysis with end-stage renal disease at the age of 24, and underwent first kidney transplantation at the age of 28. When peritoneal dialysis (PD) was induced due to the worsening kidney function at the age of 50, the serum intact parathyroid hormone (iPTH) level remarkably increased (2332 pg/mL). Although cinacalcet was administered, the patient’s iPTH levels were not sufficiently suppressed for seven years. Diagnostic images including ultrasound, computed tomography, and (99m)Tc-methoxyisobutylisonitrile scintigraphy indicated THPT as the reason for prolonged post-transplant hypercalcemia. Therefore, PTX was performed 14 months after the second transplantation. Histology showed nodular hyperplasia of all parathyroid glands, indicating autonomous secretion of parathyroid hormone. In general, patients with more severe THPT are recognized with more severe SHPT prior to transplantation during the dialysis period. We should consider a referral for surgery based on the individual risk factors. We recommend to perform parathyroidectomy earlier, before the kidney transplantation in the clinical suspicion of severe SHPT.